PELATIHAN PENGEMBANGAN GAMIFIKASI PEMBELAJARAN UNTUK PENGUATAN KEGOTONGROYONGAN KOLABORATIF : PELATIHAN PENGEMBANGAN GAMIFIKASI PEMBELAJARAN UNTUK PENGUATAN KEGOTONGROYONGAN KOLABORATIF - Wicaksono, Vicky Dwi; Paksi, Hendrik Pandu; Wijoyanto, Danang; Puspita, Ari Metalin Ika; Wardani, Helda Kusuma (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2024)
Training on developing learning gamification aims to strengthen collaborative cooperation among teachers and students in elementary schools. This training focuses on increasing teachers' understanding and skills in designing and implementing gamification elements that encourage cooperation, collaboration and social interaction in learning. Through the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, this training provides a systematic approach in developing technology-based and non-digital learning gamification. Training activities are carried out using blended learning, which combines offline and online learning to provide flexibility and effectiveness in implementation. The results of this training show a significant increase in teachers' ability to integrate gamification in learning, as well as building sustainable learning communities in schools. The results of the PKM implementation questionnaire showed that 91.7% of teachers were helped by this training. The suitability of the material to the needs received a score of 92.8%, the method of delivering the material was 94.2%, the follow-up to complaints or questions was good at 91.4%, and the indicator of increasing the professional and pedagogical competence of partners/participants was 93.5% . This training not only strengthens teacher competence in using educational technology but also strengthens the values ​​of mutual cooperation among students, thereby creating a more collaborative and inclusive learning environment. Keywords: Gamification, Mutual Cooperation, Collaboration